2021
DOI: 10.24036/0202151107569-0-00
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Probiotic Candidate Lactic Acid Bacteria (Lab) from Shrimp Paste (Mysis relicta) Based on 16s rRNA Gene

Abstract: Terasi is one of the fermented product of shrimp or fish which is often used as food seasoning by the people. Terasi is also a source of Lactic Acid Bacteria (LAB) which has the potential as a culture for probiotic starters. Probiotics are dietary supplements containing live microbes that profitable to their hosts. This study aimed to identify probiotic lactic acid bacteria isolated from terasi of shrimp based on the 16S ribosomal ribonucleic acid (rRNA) gene sequence. LAB isolation from terasi was done by pou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Figure 3 illustrates the processing of terasi. Identification of microbial composition reported that terasi comprised lactic acid bacteria such as Enterococcus faecalis, Bacillus subtilis, Weissella cibaria, and Pediococcus acidilactici [7,31,32].…”
Section: Terasimentioning
confidence: 99%
“…Figure 3 illustrates the processing of terasi. Identification of microbial composition reported that terasi comprised lactic acid bacteria such as Enterococcus faecalis, Bacillus subtilis, Weissella cibaria, and Pediococcus acidilactici [7,31,32].…”
Section: Terasimentioning
confidence: 99%
“…Probiotics are mainly found in native fermented food from Indonesia, such as bekasam (Sari et al 2018), terasi (Putra and Resti 2018;Fevria et al 2023), tape and tempeh (Sulistiani et al 2019;Azizah et al 2021), and oncom (Kurniati et al 2021). Probiotics, known by the community, are commonly produced as drinks, such as cow milk, buffalo milk, cheese, and yogurt (Karami et al 2017).…”
Section: Introductionmentioning
confidence: 99%